2018
DOI: 10.1108/josm-12-2016-0318
|View full text |Cite
|
Sign up to set email alerts
|

Flow revisited: process conceptualization and a novel application to service contexts

Abstract: Purpose Flow is an important yet under-utilized concept to examine extraordinary experiences in service encounters. An extensive review of extant literature revealed several conceptual concerns that have contributed to a blurred understanding of flow. The purpose of this paper is to develop a conceptualization of flow that is complete yet parsimonious. Design/methodology/approach The paper includes a survey (Study 1, N=202) that covers gaming and online services and a field study (Study 2, N=448) covering a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 134 publications
0
19
0
Order By: Relevance
“…Some flow antecedents in CMEs relate to the connection between the person and the task. The review of identified articles shows that, among person‐task antecedents, the balance between task challenges (task‐related factor) and the individual's skills (person‐related factor) in performing the task, is the most studied factor leading to flow (e.g., Drengner et al., 2018; Guo et al., 2016; Wang & Hsu, 2014). Individuals' perceived control, which is the extent to which individuals can control their actions (person‐related factor) in completing a task (task‐related factor) (Agarwal & Karahanna, 2000), is the second most studied factor leading to flow in this category.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some flow antecedents in CMEs relate to the connection between the person and the task. The review of identified articles shows that, among person‐task antecedents, the balance between task challenges (task‐related factor) and the individual's skills (person‐related factor) in performing the task, is the most studied factor leading to flow (e.g., Drengner et al., 2018; Guo et al., 2016; Wang & Hsu, 2014). Individuals' perceived control, which is the extent to which individuals can control their actions (person‐related factor) in completing a task (task‐related factor) (Agarwal & Karahanna, 2000), is the second most studied factor leading to flow in this category.…”
Section: Resultsmentioning
confidence: 99%
“…As the literature on flow advances, researchers provide more clarity on flow and propose a process model of flow. These researchers believe that flow is not an immediate state rather a process that starts from three pre‐conditions: challenge‐skill balance, feedback and clear goals, ending with enjoyment (Drengner et al., 2018; Pearce et al., 2005). The assessment of literature shows that when studying flow, some studies use all nine conditions (e.g., Chen et al., 2000; Siemens et al., 2015), while others consider fewer conditions consisting of two (e.g., Chen et al., 2018), four (e.g., Jeon et al., 2018), five (e.g., Drengner et al., 2018) and six conditions (e.g., Guo & Poole, 2009), drawn from Csikszentmihalyi's flow model.…”
Section: Flow Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Flow considers a broad set of psychological states as it includes affective and cognitive dimensions. In particular, enjoyment is widely seen as a core dimension of flow experiences (Drengner, Steffen, and Furchheim 2018). The focus of immersion is, however, centered on a person’s concentration on the task at hand (i.e., a cognitive dimension).…”
Section: Theoretical Backgroundmentioning
confidence: 99%